Investigation of effects of different media on CHO cell growth and production of IGFI - Hashim, Yumi Zuhanis Has-Yun ([s.n], 2012)
Different media is formulated with varied concentration of nutrients resulting in different cell growth behaviour and productivity of the system. The objective of the study was therefore to investigate the effects of different media on CHO-K1 cell growth and production of Insulin-like Growth Factor-1 (IGF-1) towards identifying the optimal media for further use. CHO-K1 were cultured in Ham's 12 and RPMI media respectively. Samples were collected at designated time intervals for cell counting, biochemical analysis and determination of biomass, total protein as well as IGF-1 concentration. Both univariate and multivariate data analysis (MVDA) approach were used to analyse data. Using univariate analysis, RPMI gave higher saturation density (9.13 x 10^5 cells/ml) and IGF-1 (31.56 pg/ml) concentration when compared to Ham's 12 (saturation density: 8.65 x 10^5 cells/ml; IGF-1: 29.87 pg/ml). Meanwhile MVDA showed that culture was clearly separated by types of media. Interestingly, glucose utilization was shown to possibly cause the separation rather than cell number related observations. Taken together, RPMI was suggested as a better choice for CHO-K1 culture since it enabled the culture to efficiently consume glucose to yield high cell saturation density and IGF-1. In addition, glutamine and IGF-1 was observed to have positive correlation which warrants further research.